Assessment of work-related health hazards, personal hygiene and utilization of personal protective equipment’s among stone quarry workers: a cross sectional study in Central India - Prasad, Manish A.; Verma, Nirmal; Jain, Kamlesh; Dewangan, Pradeep (International Journal Of Community Medicine And Public Health, 2019)
Background: It is estimated that exposures in the workplace account for around one in ten cases respiratory morbidities in adulthood. Being a respiratory ailment, this group of disorders impairs the pulmonary functions. The objective of the study was to assess the work-related health hazards, personal hygiene and utilization of personal protective equipments among stone quarry workers in Wardha district in Maharashtra. Methods: This cross sectional study was conducted among 348 subjects working in the stone quarries situated in Yelakeli, Deoli, Paloti, Pulgaon, Borgaon, Nachangaon in Wardha district in Maharashtra. Results: 114 (32.75%) of the people reportedly had respiratory problems, body ache was reported by 154 (44.2%), eye problem was reported by 66 (18.9%), fever was told by 13 people (3.7%), other problems (like hearing related, skin, GIT etc) reported were 14 (4.02%). Chi-square test was found to be non-significant. Conclusions: None of the workers had undergone pre-placement examination. Personal protective measures are rarely used by stone quarry workers.